Checklistor i sjöfarten - En kvalitetsstudie - Persson, Tom; Rydberg, Alexander (My University, 2017)
Today, checklists are used in a variety of professional fields where complex situations and activities are common. For example, checklists are found to be an important component in commercial aviation as well as in surgery and medicine. In these areas, the procedure of using checklists has shown to an increase in safety when applied correctly. In the shipping industry, a frequent usage of checklists in the daily work on board has become well established and accepted. Through previous research, it has been determined that there is a lack for common criteria regarding systematic design of checklists within the shipping industry. This report intends to determine the level of quality that is to be found in checklists used in commercial shipping from a design and structural perspective. To answer this question a documentary survey were made. Checklists were collected using an exploratory sample of shipping companies with Swedish connection. Furthermore, a literature study was conducted in order to establish general criteria for good design of a checklist and what components should be included in a checklist. The criteria formed the basis for a matrix that gave the checklists a score where the scores were intended to be compared with the checklist of quality in a scale of 0-15, according to the chosen criteria. The survey matrix itself were formulated as a kind of checklist where the examined checklist would get points if it complies with the criterion. The study shows that checklists assessed on the basis of the selected criteria are at an average grade of 9.7 out of 15 points. There are also a number of criteria that are met by all the checklists and criteria that are not met by any of them suggesting that the developers of the checklists have considered certain components of the checklist more important than others.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport